A primary study of density and compressive strength of the silicon nitride and titanium nitride ceramic composite. (2020) - Vivekananthan, M.; Ahilan, C.; Sakthivelu, S.; Saravanakumar, M.
Abstract: Now a day most of the automobile components and biomaterials are made from ceramic matrix composites due to the high bearing load, High fracture toughness, high temperature resistance and high hardness for that the application of knee and hip implants are made of that material. In this study, we developed the unique manufacturing process of the Titanium nitride in the silicon nitride matrix is established. The Silicon nitride- Titanium nitride is a novel material composite is manufactured by the conventional powder forming process. Titanium nitride is added to the silicon nitride in the various wt% and compressed by the cold pressing and sintered by the BOX furnace in the temperature between 1400 °C and 1600 °C that ceramic composite pellets were made. The physical characteristic density of the sintered ceramic pellets was resolved by Archimedes principle and theoretical density were compared. The density of the composite was studied primarily to evaluate the structural steadiness of the composite. Compressive strength of the material is calculated by the compressive testing machine.